Perceived value, service quality, trust, and repurchase intention: satisfaction as a mediator in the market for commercial contraceptives - NL Rina Budiarti; Akhmad Saufi; Dwi Putra Buana Sakti (Jurnal Konseling dan Pendidikan, 2025)
Commercial contraceptives represent a growing segment in family planning, yet evidence on what drives consumers to consistently repurchase these products remains limited, especially in emerging markets. This study addresses a theoretical gap in health marketing by examining how perceived value, service quality, and trust shape repurchase intention, with customer satisfaction as a mediating mechanism. A cross-sectional survey was conducted involving 381 reproductive-age wives (15–49 years) using injectable, implant, or IUD contraceptives in North Lombok, Indonesia, selected through systematic random sampling. Respondents varied in education and employment status to reflect real market diversity. All constructs were measured using validated Likert-scale instruments with reliability and validity confirmed through composite reliability and AVE thresholds. Data were analyzed using SEM-PLS (SmartPLS) to test hypotheses and mediation effects. The results show that trust has the strongest effect on repurchase intention ( P value= 0.011), followed by service quality (P value= 0.011) and perceived value (P value= 0.032). These findings imply that strengthening trust through credible information, consistent product quality, and reliable service delivery can enhance consumer loyalty. Private healthcare providers and distributors should improve counseling and service experience to differentiate commercial products from government-subsidized options. While offering policy insights on cost reduction and self-reliant family planning, this study acknowledges limitations related to its single-location and cross-sectional design, suggesting caution in generalizing results. Future research should expand across diverse regions and contraceptive types to enrich understanding of consumer behavior in the contraceptive market.